The implications of the green constitution movement program in creating law awareness for river border community - Fitriasari, Susan; Budimansyah, Dasim; Insani, Nisrina Nurul; Tresnayadi, Sandra (Universitas Negeri Yogyakarta, 2022)
Humans and the environment are two elements that should coexist. All levels of society should own related awareness of maintaining the environment. However, in reality, the river border community's awareness of the importance of preserving the environment is still lacking. One of the triggering factors is the lack of public legal awareness about the environment. the Green Constitution echoes the regulation of human rights to the environment in the state constitution as a commitment to environmental protection and management. The purpose of this activity is to foster an understanding of the legal awareness of the river coast community about the environment, understanding of regulations or alternative environmental policies on the river coast, and the community's ability as a pioneer of environmental law. The research method used in this study is using a qualitative approach. Data collection techniques by participant observation and focus groups discussion. Data analysis techniques with qualitative descriptive analysis techniques. The expected outcome is that the residents of the riverbank communities will gain advanced knowledge and understanding of legal awareness to protect the environment through the Green Constitutions program.